EVALUATION OF REACTION OF VILLAGE PLANNING AND BUDGETING ONLINE TRAINING PARTICIPANTS AT THE FINANCE TRAINING CENTER OF MALANG - M. Bahrun Nawawi (Yayasan Hurriah, Banda Aceh, 2023)
Evaluation is required to determine the success of training in increasing employee competence and performance. The purpose of this study is to determine the attitudes of participants and instructors to the implementation of online village planning and budgeting training batch 1 of 2022 at the Malang Financial Education and Training Center. Donald L. Kirkpatrick's level-1 Kirkpatrick four levels evaluation model was used to undertake training evaluation. This is a quantitative descriptive study that employs a survey method. The findings revealed that the learners' attitude to the implementation and the instructors of the online village planning and budgeting course was quite positive. This is demonstrated by the participant's assessment of the implementation process, which received an average score of more than 4.6, and the participant's assessment of the instructor, which received an average score of more than 4.5. Participants suggested that this training be extended to other village apparatus, and that if the circumstance is safe, it be conducted offline at the Malang Financial Education and Training Center to maximize the outcomes.